Preparation and Chemical Characterization of Eco-friendly ORMOSIL Nanoparticles of Potential Application in DNA Gene Therapy - Colaco, Rui; Clara Goncalves, M.; Fortes, L.M.; M.D.Goncalves, Lidia; J. Almeida, Antonio; F. Martins, Barbara (Current Nanoscience, 2013)
One focus in nanotechnology is the development and use of nonviral vectors for safe and efficient gene delivery. Inorganic and organically modified silica nanoparticles are chemical and biologically inert, optically transparent and can be doped with imaging agents and/or functionalized to promote its conjugation with different therapeutic molecules. Silica/ORMOSIL nanoparticles can be engineered to improve diagnosis, treatment and follow-up of diseases. A combination of diagnosis devices and therapeutics (theranostics) would be beneficial for patients. In this work, ORMOSIL nanoparticles as non-viral vectors for gene delivery were prepared via a modified Stober sol-gel process directly with 3-aminopropyltriethoxysilane (APTES), methyltriethoxysilane (MTES), vinyltrimethoxysilane (VTES), N1- [3-(trimethoxysilyl)-propyl]diethylenetriamine (DETA), and tetraethylorthosilicate (TEOS) as precursors. Dynamic light scattering, transmission electron microscopy and Fourier transformed infrared spectroscopy were used to characterize the ORMOSIL nanospheres. Synthesis has been optimized and monodisperse spherical nanoparticles with desired size have been obtained. Nanoparticle-DNA complexes were successfully obtained at different ratios (nanoparticle/pDNA) and confirmed by agarose gel electrophoresis and ethidium bromide exclusion test.
Keywords: gene therapy